2022
DOI: 10.1007/s13555-022-00864-1
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Alopecia Areata-Related Emotional Symptoms with Work Productivity and Daily Activity Among Patients with Alopecia Areata

Abstract: Introduction Patients with alopecia areata (AA) experience psychological and psychosocial symptoms including depression, anxiety, anger, social withdrawal, embarrassment, and low self-esteem. While multiple studies have measured the detrimental emotional impact of AA on patient quality of life, evidence of its effect on work productivity loss (WPL) and daily activities is limited. This study aimed to assess the extent of AA-related emotional symptom (ES) burden on work productivity and activity im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…Our study found that productivity loss was largely a result of impaired productivity while at work (presenteeism) with only small losses resulting from absences from work (absenteeism). This was comparable with results found in the US 27,28 . The trend is also similar to reports in Japan for other chronic skin conditions such as atopic dermatitis 39,41–43 and psoriasis 44,45 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our study found that productivity loss was largely a result of impaired productivity while at work (presenteeism) with only small losses resulting from absences from work (absenteeism). This was comparable with results found in the US 27,28 . The trend is also similar to reports in Japan for other chronic skin conditions such as atopic dermatitis 39,41–43 and psoriasis 44,45 .…”
Section: Discussionsupporting
confidence: 90%
“…This was comparable with results found in the US. 27,28 The trend is also similar to reports in Japan for other chronic skin conditions such as atopic dermatitis 39,[41][42][43] and psoriasis. 44,45 43 In our study, the respective values were 0.9 ± 2.8%, 23.9 ± 25.7%, 24.3 ± 25.8%, and 35.0 ± 29.5%.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…One recent study demonstrated that employers feel less comfortable hiring individuals with AA [3]. These employer attitudes in combination with workplace bullying may contribute to the higher rates of work absenteeism, work productivity loss, and unemployment in patients with AA [6,7]. The culmination of psychosocial obstacles in the workplace and potentially lost income can compound the financial burden and distress experienced by this patient population [7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…These employer attitudes in combination with workplace bullying may contribute to the higher rates of work absenteeism, work productivity loss, and unemployment in patients with AA [6,7]. The culmination of psychosocial obstacles in the workplace and potentially lost income can compound the financial burden and distress experienced by this patient population [7][8][9]. Thus, future work needs to identify how to reduce bullying against patients with AA through education and awareness and to explore the impact of improved treatments and psychosocial support.…”
Section: Discussionmentioning
confidence: 99%